PENGARUH VARIASI BENTUK FLAME HOLDER TERHADAP KARAKTERISTIK NYALA API PADA PEMBAKARAN MESO SCALE COMBUSTOR - Mochammad Khoirul Rosidin; Yuliati, Lilis; Winarto, Winarto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
This study used an experimental method by directly observing the object under study. The independent variables in this study include the geometry of the flame holder on the meso-scale combustor, airflow, and fuel discharge. The research data were analyzed and displayed in graphical form as well as flame visualization. This research concludes that combustion using a flame holder circle has a more stable and even flame compared to a flame holder concentric ring and backward facing step. The shape of the Flame holder circle also produces a higher flame temperature. The results of this study contribute to the development of MPG based on micro combustion with a better understanding of the interaction between flame holders, reactant velocities and equivalent ratios in achieving stable and efficient combustion in meso-scale combustors. This research can provide important input for the development of high-efficiency micro-combustion-based power generation technology in the future.